2020
DOI: 10.1007/s13318-020-00651-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Verapamil, a P-gp Inhibitor, on the Pharmacokinetics, Safety, and Tolerability of Omadacycline in Healthy Adults: A Phase I, Open-Label, Single-Sequence Study

Abstract: Background Omadacycline is a semisynthetic aminomethylcycline antibacterial derived from the tetracycline class. It is approved in the USA to treat adults with acute bacterial skin and skin-structure infections and community-acquired bacterial pneumonia. Objectives This phase I, open-label study evaluated the effect of a potential drug–drug interaction of verapamil—a known P-glycoprotein (P-gp) inhibitor—with omadacycline on the pharmacokinetic profile of omadacycline i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
(19 reference statements)
2
8
0
Order By: Relevance
“…Verapamil was utilized in this study to confirm the contribution of P‐gp efflux transporters to poor lisinopril permeability. According to the FDA guidance recommendation, verapamil was reported as a potential P‐gp inhibitor (Hunt et al., 2021; Wang & Sun, 2020). The influence of coperfusion of verapamil on lisinopril absorption was investigated in the duodenum and ileum segments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Verapamil was utilized in this study to confirm the contribution of P‐gp efflux transporters to poor lisinopril permeability. According to the FDA guidance recommendation, verapamil was reported as a potential P‐gp inhibitor (Hunt et al., 2021; Wang & Sun, 2020). The influence of coperfusion of verapamil on lisinopril absorption was investigated in the duodenum and ileum segments.…”
Section: Resultsmentioning
confidence: 99%
“…It may exert its action via modulating intestinal membrane dynamics and permeability characteristics facilitating drug absorption through the intestinal barrier (Gohil & Mehta, 2009; Khajuria et al., 1998, 2002). Verapamil was selected due to its reported P‐gp inhibitory effect (Hunt et al., 2021; Wang & Sun, 2020). This may aid in investigating the contributing role of P‐gp efflux transporter in limited lisinopril permeability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary hepatocytes of chicken embryo inoculated in 24-well plates were cultured to about 80% confluency. Cells were treated with metyrapone (500 μM) alone or combined with 100 μM verapamil, a specific P-gp inhibitor [ 32 , 33 , 34 ], for 24 h, and cells without treatment were used as the control. The cells were washed twice with PBS and then incubated with 5 μM Rho123, a selective P-gp substrate [ 35 , 36 , 37 ], for 60 min.…”
Section: Methodsmentioning
confidence: 99%
“…VER at concentrations of 6.0–10.0 μmol/L exerts effective reversal effect on tumor drug resistance and can improve the clinical efficacy of chemotherapy for hepatocellular cancer, colon cancer, lung cancer, and malignant ascites ( Liu et al., 2011 ). Studies have shown that the reversal effect mechanism of VER in MDR in tumors is likely related to P-glycoprotein (P-gp) ( Gao et al., 2021 ; Hunt et al., 2021 ). VER resists MDR in tumors by regulating the expression of P-gp.…”
Section: Introductionmentioning
confidence: 99%